Possibilia: Possible Worlds and the Limitless in Architecture - Sean Pickersgill (Footprint)
Speculative architectural projects, by definition, challenge the viewer to understand the relationship between the fictionalised world they portray and the possible states of affairs that have come into existence for the project to ‘exist’. It is the question of how a speculative project can ‘exist’ in our understanding of the world in a meaningful, non-trivial fashion that is the subject of this article. Employing some basic structural clarity from contemporary modal logic, and from studies in fictionality, it is possible to see a renewed value in the ‘worlds’ that speculative projects describe, and to understand the profound philosophical value in imagining an existence in an ‘other’ world.